Analyzing the Association of Social Capital and Sleep Quality of the Elderly Community - Maryam Mohammadi; Sahar Mohammadnabizadeh; Mehdi Varmaghani; Mitra Moodi; Farshad Shrifi; Matin Shirazinia; Hossein Fakhrzadeh; Moloud Payab; Masoumeh Khorashadizadeh; Shohreh Naderimagham (Health Science Reports)
ABSTRACT Purpose Given the growing elderly population in developing countries like Iran, and the significance of social capital and sleep quality in the lives of the elderly, this study aimed to explore the relationship between social capital and sleep quality in the elderly community. Patients and Methods This cross‐sectional study was conducted on elderly individuals in Birjand city, Iran, as part of a cohort study. Sampling was carried out by selecting eligible participants based on a simple random entry criterion. To gather data, we used questionnaires on social capital and Pittsburgh Sleep Quality, which were validated for reliability. The questionnaires were administered through interviews. The data was analyzed using STATA software and appropriate descriptive and analytical tests. Results A total of 1348 senior citizens, with an average age of 69.73 (±7.53), were involved in the research conducted. The results of this study revealed a significant association (p < 0.05) only in the fifth quintile of social capital when compared to the lowest level. These results also show that the social capital in the group that sleeps more than 6 h is stronger than the group that sleeps less than 6 h. Also, married people in each group with less sleep (RR = 0.92) or more than 6 h (RR = 0.66) had a better condition than single people. Conclusion Improving healthcare availability, implementing intervention strategies such as community and public health initiatives, promoting healthier sleep habits, and enhancing social support are potential methods to prevent low social involvement and, consequently, poor quality of sleep‐in older people.